Development of an adaptative human-robot interface based on physiological parameters to promote physical activity in sedentary participants (2023)
The lack of adherence to exercise is a key issue in public health. Among current technological solutions, socially assistive robots have been implemented as a strategy to increase the motivation of people to exercise. However, by integrating these technologies is not aimed just to fill the proposed task, but to make the human-robot interaction as natural as possible. With this purpose, a system composed of an adaptative human-robot interface was developed. The system is composed of three modules: i) a social robot ii) graphical user interface (GUI), and a iii) heart rate sensor, which were interconnected with each other with the aim to use the robot as a support tool for an exercise session